Analysis of Junior High School Social Studies Teachers' Strategies in Facing the Demands of the Society 5.0 Curriculum Era (A Study in the City of Banda Aceh) - Putri*, Hanif Nafyza; Mawardi, Mawardi; Haikal, Muhammad (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This research aims to describe the implementation of junior high school social studies (IPS) learning in the era of Society 5.0 in Banda Aceh City in facing curriculum demands, analyze the strategies of junior high school IPS teachers in enhancing their own competencies, and describe the solutions that junior high school IPS teachers employ to overcome challenges in facing the curriculum demands of the Society 5.0 era. This research utilizes a qualitative approach with a case study design. Data collection techniques include interviews and documentation. Data analysis techniques include data reduction, data presentation, verification, and drawing conclusions. The results of the research indicate that the models and methods of IPS learning in junior high schools in Banda Aceh City during the Society 5.0 era demonstrate creativity by implementing various learning models and integrating technology, such as discovery learning, project-based learning (PBL), and discussions using media such as Canva, picture and picture, and employing a differentiation approach, among others. Junior high school IPS teachers enhance their competencies through activities such as MGMP (Teacher Subject Study Group), FORGIPSI (Forum Guru IPS Indonesia), and online self-learning, focusing on collaboration, technology integration, and the development of critical thinking skills. Solutions that junior high school IPS teachers can take include active participation in training activities, webinars, seminars, and collaboration among teachers. Despite limitations in IT facilities, teachers continue to make efforts to create an effective learning environment while motivating themselves to adapt to the future development of students.